Land-use Conservation Assessment and Its Influence on Rainfall Erosivity Distribution - MOHD SYAZWAN, MUHAMMAD ASYRAF (Universiti Teknologi PETRONAS, 2017)
Cameron Highlands in Malaysia is about 1,000 metres above sea level with high rainfall intensity characteristics which about 2500-3000mm annually. Massive agricultural activities had took place on the highlands along with rapid urbanisation process over the years. Unfortunately, those have caused soil erosion problem on Cameron Highlands and has become eminent threat by washing away natural topsoil over the area. There are two factors governing soil erosion which are natural and anthropogenic. In this research, natural factor by means of rainfall or precipitation will be considered. Rainfall intensity governs the rainfall erosivity, which by definition is the kinetic force causing soil detachments and being washed away.